Geochemistry of the Sykesville diamictite in central Maryland: an investigation of clast-matrix activity during metamorphism with tectonic implications - Tamburro, Edie T. (Virginia Polytechnic Institute and State University, 1986)
The Sykesville diamictite is part of the Wissahickon sequence, a polydeformed and metamorphosed sequence of questionable age in the Central Appalachian Piedmont. It occurs in association with thrust stacks of volcanic and mafic units of the Baltimore Mafic Complex and Potomac Valley Sequence in Maryland and Virginia, which are responsible for its formation. The matrix in central Maryland and northern Virginia is a schistose to massive granofelsic unit at biotite garnet grade. It contains fragments of quartz, pelitic schist, felsic-gneiss, mafic schist, amphibolite, and metacalcareous rocks. Sharp contacts and mineral chemical affinity between the matrix and pelitic schist and some felsic-gneiss clasts suggests that these inclusions were intrabasinally derived as first suggested by Fisher (1970). Zoned textures, compositional differences, and isotopic disequilibrium with the matrix exhibited by mafic schist, amphibolite, and amphibole-bearing felsic-gneiss clasts suggests these inclusions were derived directly from the allochthon responsible for generating the diamictite. The amphibolite and amphibole-bearing gneisses show textural and mineral chemical affinity with the Baltimore Mafic Complex. Rb-Sr mineral ages suggest the metamorphism in the diamictite matrix is Hercynian. Ordovician ages are estimated for some of the felsic-gneiss and pelitic clasts. Combining these data with existing data for the Wilmington Complex (Grauert and Wagner, 1975), the Bear Island Granite (Muth et. al., 1979), thrusting in northeastern Maryland (Lesser, 1982), and plutonism in the Maryland Piedmont (Sinha, et. al., 1979), suggests deposition of the Sykesville diamictite is Ordovician. Following deposition and overthrusting, a thermal event at 300 my generated the Gunpowder Granite (Olsen, 1972; Grauert, 1973a; Sinha et. al., 1979), and produced the observed metamorphism in the Sykesville diamictite matrix. This model is at variance with a Penobscotian deposition (Drake, 1985a). M.S.